(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Studies were carried out to determine the phytochemicals and the antibacterial activity of Senna occidentals, it is a shrub that grows between 5 to 8cm in height, it is an important member of the plant family Fabaceae and the subfamily Caesalpiniaceae and commonly found in the tropics. S. occidentalis leaves were collected in September, 2017 at flowering stage, the sample was air-dry at room temperature, the dried leaves were powdered and stored in an air-tight container for further use. The ethanolic, petroleum Ether and aqueous extracts were made by transferring 50g of the powder into 150ml of the solvents respectively and allowed to soak for four days; it was filtered using a filter paper. The results obtained from the research reveals that S.occidentalis contains certain phytochemicals such as anthraquinones, flavonoids, alkaloids, saponins, terpenoids, and Tannins which are responsible for the antibacterial activity of the plant; suggesting its potential use in the production of a new brand of antibiotic